REVIEW ON VEHICLE STEER-BY-WIRE TECHNOLOGY - Lokesh Kumar Chaudhary, Abhijeet Kumbhar (International Journal of Research Science and Management, 2015)
There is much advancement in steering control technology with time. Steering –by-wire (SBW) system is the most modern and efficient technique, the steer-by-wire is replacing the traditional steering device of the vehicle in which the conventional steering system is replaced by electronic system. This paper focus to introduce steer-by-wire technology and methodology and angle sensor is preferred to have the good accuracy. Finally steer-by-wire technology is better than conventional system with respect to their advantage over conventional system.